Penggunaan Metode Bioassay untuk Mendeteksi Pergerakan Herbisida Pascatumbuh Paraquat dan 2,4-D dalam Tanah - Nanik Sriyani; Abdul Kadir Salam (JOURNAL OF TROPICAL SOILS, 2008)
A simple and cheap method to detect herbicide residue in soil and water is urgently needed as the quantity and frequency of herbicide usage is steadily increasing in Indonesia which raises concern about the effects of herbicide residue in soil and water.  This study is the third step from a series of studies aim to develop bioassay technique to detect the present and quantity of herbicides in soil and water.  In this study, bioassay was used to detect movement of paraquat and 2,4-D herbicides in soil.  Study was carried out using soil column method.  Treatments were arranged factorially in a completely randomized block design with 3 replicates.  Two ultisol soil types: Podsolik Merah Kuning (PMK) and Latosol Coklat (LC) and 2 post emergence herbicides: paraquat and 2,4-D, were tested.  To calculate the amount of herbicide using bioassay, each standard curve for paraquat and 2,4-D were developed.  Using these standard curves, the amount of paraquat and 2,4-D was calculated based on the growth rate of caisim as indicator plant.  Results showed that bioassay method can be utilized to detect herbicide movement in soil.  The amount and the rate of herbicide movement were determined by soil and herbicide types.  In PMK, paraquat reached the depth of 20-30 cm at 2 weeks after application (WAA), however, after that the amount of paraquat found was very limited.  In LC, the movement of paraquat was more limited compared to its movement in PMK.  Paraquat reached soil depth of 10-20 cm at 2 WAA, afterward paraquat was only detected in soil depth of 0-10 cm.  Similar pattern was observed for 2,4-D which reached soil depth of 30-40 cm at 1 WAA in PMK.  In LC, 2,4-D movement was more limited.  At 2 WAA, 2,4-D in LC reached soil depth of 30-40 cm in limited amount and after 12 WAA the herbicide was detected only at soil depth of 0-10 cm.